2014
DOI: 10.1093/gerona/glu073
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes and Antidiabetic Medications in Relation to Dementia Diagnosis

Abstract: Diabetes is associated with an increased risk of dementia. The risk effect becomes weaker provided that participants take sulfonylureas or metformin rather than thiazolidinediones for a longer period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
144
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(150 citation statements)
references
References 19 publications
2
144
0
2
Order By: Relevance
“…From a retrospective study, hospital-admitted T2DM patients had a relative risk (RR) of 1.37 for dementia compared to controls [4]. By contrast, the RR for dementia diagnosis was 1.56 among newly onset T2DM patients compared to those participants without T2DM [5]. The increased risk for dementia in T2DM patients was associated with many factors (Table 1), including age [6,7], apolipoprotein E (APOE) ε4 carrier status [6], and medications, such as oral hypoglycemic agents and use of statins (lipid metabolism modifying agent) [6].…”
Section: T2dm As a Risk Factor For Dementiamentioning
confidence: 99%
“…From a retrospective study, hospital-admitted T2DM patients had a relative risk (RR) of 1.37 for dementia compared to controls [4]. By contrast, the RR for dementia diagnosis was 1.56 among newly onset T2DM patients compared to those participants without T2DM [5]. The increased risk for dementia in T2DM patients was associated with many factors (Table 1), including age [6,7], apolipoprotein E (APOE) ε4 carrier status [6], and medications, such as oral hypoglycemic agents and use of statins (lipid metabolism modifying agent) [6].…”
Section: T2dm As a Risk Factor For Dementiamentioning
confidence: 99%
“…Observational studies show reductions in mild cognitive impairment (MCI) [52] and dementia [53,54] among participants with diabetes taking metformin when compared with no medication or other glucose-lowering agents. For example, a Taiwanese study in individuals aged ≥ 50 years found that metformin use significantly decreased the risk of dementia compared with no medication (HR 0.76 [95% CI 0.58, 0.98]) [51].…”
Section: Clinical Impact Of Metformin Beyond Glycaemic Controlmentioning
confidence: 99%
“…The literature search yielded six qualified studies [18,19,20,21,22,23]. Figure 1 shows the process of studies being included and excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of the included studies and comparisons are shown in table 1. In three studies [19,21,23], data of participants treated with monotherapy and combined therapy were both displayed, and as mentioned above, data of the former were adopted. Two studies [18,23] contained both data referenced to PDnD and PnD, and as mentioned above, data of the former were adopted.…”
Section: Resultsmentioning
confidence: 99%